2013
DOI: 10.1161/circulationaha.112.000728
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Consumption With Risk of Abdominal Aortic Aneurysm

Abstract: Background-Dietary factors affecting the risk of developing abdominal aortic aneurysm (AAA) are scarcely investigated.The aim of this study was to investigate the associations of fruit and vegetable consumption with the risk to develop AAA. Methods and Results-The prospective Cohort of Swedish Men and the Swedish Mammography Cohort, consisting of 44 317 men and 36 109 women, 46 to 84 years of age at the start of the 13-year follow-up (1998-2010), were used. Fruit and vegetable consumption was assessed at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 43 publications
(55 reference statements)
4
35
2
2
Order By: Relevance
“…All regression models were stratified by age into seven 5‐year categories. Multivariable analyses were further adjusted for education (primary school, high school, university), waist circumference (less than 80, 80–87, at least 88 cm for women; less than 94, 84–101, at least 102 cm for men), alcohol consumption (grams per week in sex‐specific quartiles) and fruit consumption (servings per day in quartiles). Diabetes, hypertension, hypercholesterolaemia and CVD (angina, myocardial infarction, ischaemic stroke, heart failure or peripheral artery disease) were modelled as binary variables.…”
Section: Methodsmentioning
confidence: 99%
“…All regression models were stratified by age into seven 5‐year categories. Multivariable analyses were further adjusted for education (primary school, high school, university), waist circumference (less than 80, 80–87, at least 88 cm for women; less than 94, 84–101, at least 102 cm for men), alcohol consumption (grams per week in sex‐specific quartiles) and fruit consumption (servings per day in quartiles). Diabetes, hypertension, hypercholesterolaemia and CVD (angina, myocardial infarction, ischaemic stroke, heart failure or peripheral artery disease) were modelled as binary variables.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging epidemiological studies have shown an inverse relationship between cardiovascular disease mortality and diets rich in fruits and nuts in epidemiological studies [19][20][21][22][23]. High levels of many different phytochemicals, including polyphenols, are found in both fresh and processed fruits [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…39 Polyphenols and flavonoids enriched in fruits were found to increase the expression or activity of PONs. [40][41][42][43] Similarly, moderate alcohol consumption increases the serum high-density lipoprotein cholesterol level and PON activity 44 and is associated with a lower risk of AAA.…”
Section: Discussionmentioning
confidence: 98%